2019
DOI: 10.1002/joa3.12226
|View full text |Cite
|
Sign up to set email alerts
|

One‐year clinical outcomes of anticoagulation therapy among Japanese patients with atrial fibrillation: The Hyogo AF Network (HAF‐NET) Registry

Abstract: Background Although anticoagulation therapy could reduce the risk of strokes in patients with atrial fibrillation (AF), large‐scale investigations in the direct oral anticoagulant (DOAC) and AF catheter ablation (CA) era are lacking. Methods This study was designed as a prospective, multicenter, observational study and a total of 2113 patients from 22 institutions were enrolled in the Hyogo area. Results The mean age and CHADS2 score were 70.1 ± 10.8 years old and 1.5 ± 1.1, respectively. The follow‐up period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
5
0
2
Order By: Relevance
“…A pooled meta-analysis of these studies demonstrated a hazard ratio of 0.60 (95% confidence interval 0.42–0.88, p < 0.05 with an I 2 value of 50%). Hyogo et al found that new onset dementia occurred in 8 of 2113 (0.4%) atrial fibrillation patients [ 18 ]. In the 614 patients who had been treated with catheter ablation, 3 (0.5%) had developed dementia over the 1 year follow up period.…”
Section: Resultsmentioning
confidence: 99%
“…A pooled meta-analysis of these studies demonstrated a hazard ratio of 0.60 (95% confidence interval 0.42–0.88, p < 0.05 with an I 2 value of 50%). Hyogo et al found that new onset dementia occurred in 8 of 2113 (0.4%) atrial fibrillation patients [ 18 ]. In the 614 patients who had been treated with catheter ablation, 3 (0.5%) had developed dementia over the 1 year follow up period.…”
Section: Resultsmentioning
confidence: 99%
“…Hyogo et al 24 acompanharam 2113 participantes com FA por 1 ano, com o objetivo de avaliar os desfechos primários (infarto cerebral sintomático, incluindo ataque isquêmico transitório, embolismos sistêmicos e complicações hemorrágicas fatais necessitando de hospitalização) e secundários (novos sinais de demência, eventos cardíacos que causam hospitalizações e outras causas de morte, sendo que o diagnóstico de demência foi dado pelo miniexame do estado mental e/ou Hasegawa) em pacientes que faziam uso de NOACs e varfarina. Como resultado, concluiu-se que, os desfechos primários foram encontrados em nove (1,3%) dos usuários de NOAC e em 15 (2,2%) dos usuários de varfarina.…”
Section: Discussionunclassified
“…Já os desfechos secundários, foram encontrados em 24 (3,6%) dos usuários de NOAC e em 36 (5,4%) dos usuários de varfarina. A incidência de novo início de demência, não diferiu entre os usuários de NOAC e varfarina (1 [0,1%] vs. 3 [0,4%] de 667 pacientes, P = 0,32) 24 .…”
Section: Discussionunclassified
“…Anticoagulant drugs were used in 86% and DOACs in half of the patients with anticoagulants. 1 After the release of the DOACs, two clinical multicenter registry studies on AF were studied in Japan. 2,3 In the Fushimi AF Registry, where the patients were en- The SAKURA AF Registry also showed no significant difference in the rate of the strokes/systemic embolisms and the major bleeding rate between the DOACs and warfarin users (1.2% vs 1.8%/year and 0.5% vs 1.2%/year, respectively).…”
Section: The Haf-net (Hyogo Atrial Fibrillation Network)mentioning
confidence: 99%
“…Almost 30% of the enrolled patients had a history of catheter ablation. Anticoagulant drugs were used in 86% and DOACs in half of the patients with anticoagulants . After the release of the DOACs, two clinical multicenter registry studies on AF were studied in Japan .…”
mentioning
confidence: 99%